PRECARIOUS LIFE, JUDGMENT AND A STORY OF A STORK (The Pretoria Student Law Review, 2021)
Judith Butler in her work Precarious life. The powers of mourning and violence published in the aftermath of September 11 argues that the event raised the ‘question … as to what form political reflection and deliberation ought to take if we take injurability and aggression as two points of departure for political life.’1 After another year filled with events and actions that showed aggressions and caused injury on global, national and sometimes on a local level very close to home we might consider exactly the question invoked by Butler. She hopes for the ‘chance to imagine a world’ with less violence and where interdependency is deemed necessary and foundational to all relations. A theme coming to the fore in the first essay of Precarious life is the rise of censorship and anti-intellectualism in the US after September 11.2 For students and academics these issues should be of a big concern. To what extent are the media, artists, authors and closer to home students and academics free to express their views — even if not censored in strict legal sense, are we silenced, disencouraged, dissuaded to speak up and speak out? Maybe even a bigger concern is not only the absence of intellectual engagement, conversation and discussion at the university but the active antiintellectualism that comes in many guises.
Keywords: Judith Butler; Precarious life; censorship; anti-intellectualism; USA; September 11